The role of maintenance therapy in the treatment of elderly non-small-cell lung cancer patients: a meta-analysis of randomized controlled trials - Zhang L; Gao S; He J (Dove Medical Press, 2017)
Liangzhe Zhang, Shugeng Gao, Jie He Department of Thoracic Surgery, National Cancer Center/Cancer Hospital, Chinese Academy of Medical Science and Peking Union Medical College, Beijing, China Purpose: Maintenance therapy is an effective treatment strategy for advanced non-small-cell lung cancer (NSCLC). We aim to investigate whether age would affect the efficacy of maintenance therapy in the treatment of advanced NSCLC. Materials and methods: Relevant trials were identified by searching electronic databases and conference meetings. Prospective randomized controlled trials assessing maintenance therapy in elderly patients with advanced NSCLC were included. Outcomes of interest included overall survival (OS) and progression-free survival (PFS) in elderly patients with advanced NSCLC. Results: A total of 2,724 patients from 5 randomized controlled trials were included for analysis, with 897 patients aged ≥65 years and 1,577 patients aged <65 years. Single-agent maintenance therapy in elderly patients significantly improved PFS (hazard ratio [HR] 0.65, 95% CI: 0.43–0.98, p=0.04) and OS (HR 0.81, 95% CI: 0.68–0.97, p=0.024) when compared with placebo. In addition, doublet maintenance therapy significantly improved PFS (HR 0.81, 95% CI: 0.68–0.97, p=0.024) in comparison with single-agent maintenance therapy. However, doublet maintenance did not improve OS in comparison with single-agent maintenance therapy (HR 1.05, 95% CI: 0.60–1.83, p=0.86). Conclusions: The findings of this study suggest that single-agent maintenance therapy in elderly patients with advanced NSCLC offers an improved PFS and OS when compared with placebo. Further trials are recommended to clearly investigate the efficacy of combination maintenance therapy for advanced NSCLC in this setting. Keywords: non-small-cell lung cancer, maintenance therapy, elderly, meta-analysis, lung neoplasm, older, systematic review